2014
DOI: 10.1021/la503513s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anions on the Electrodeposition of Cobalt on Pt(111) Electrode

Abstract: Voltammetry and in-situ scanning tunneling microscopy (STM) were used to examine electrodeposition of cobalt (Co) on a stationary Pt(111) electrode in 0.1 M K2SO4 + 1 mM H2SO4 + 10 mM CoSO4 (or the sulfate solution) without and with 10 mM chloride (the chloride solution). Under- and overpotential deposition (UPD and OPD) of Co resulted in reduction peaks at -0.52 and -0.74 V (vs Ag/AgCl), respectively. Hydrogen evolution was the major obstruction to Co(2+) reduction, which limited the efficiency of Co depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…2D growth is often desired in many applications for depositing a pin-hole free overlayer to cover the surface of electrodes. 2D growth has been also evidenced in the cases of Co/Au(111) 19,20 and Co/Pt(111) 21 or Fe/Au(111). 22 Among noble metals, Pd grows 2D on Au(111) [23][24][25][26] and on other substrates.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…2D growth is often desired in many applications for depositing a pin-hole free overlayer to cover the surface of electrodes. 2D growth has been also evidenced in the cases of Co/Au(111) 19,20 and Co/Pt(111) 21 or Fe/Au(111). 22 Among noble metals, Pd grows 2D on Au(111) [23][24][25][26] and on other substrates.…”
mentioning
confidence: 87%
“…43 Co electrochemical growth on Pt(111) was also studied using in situ STM. 21,[44][45][46] These studies reported 2D growth except in the presence of strongly adsorbing anions. 41 Here we present in-situ STM observations that evidence a strong potential dependent growth mode with a transition 3D → 2D growth.…”
mentioning
confidence: 99%
“…Probably, it is because chloride ions induces stress on the cobalt deposited, 31 and may interact strongly with Co adatoms yielding drastic changes on the deposit morphology. 32 Nevertheless, chloride electrolytes allow to get a higher electrical conductivity in the electrolyte, lower overpotential for cobalt deposition, and higher cathodic current efficiency.…”
Section: Introductionmentioning
confidence: 99%